Effects of Artificial Sweat Formulation and Extraction Temperature on Estimation of the Dermal Bioaccessibility of Potentially Toxic Elements in a Contaminated Soil from an E-Waste Recycling Site - Anselm, Oluwaseun H.; Davidson, Christine M.; Oyeyiola, Aderonke O.; Oluseyi, Temilola O. (Geosciences (Basel), 2022)
Informal recycling of electronic waste leads to soil contamination that can impact human health. To accurately assess exposure to potentially toxic elements (PTE) in soil it is necessary to consider their bioavailability through ingestion, inhalation and dermal contact. However, bioaccessibility tests that estimate dermal absorption following adhesion of contaminated soil particles to skin are not well established. In this study the concentrations of As, Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn were estimated in the <45 µm particle size fraction of a bulk composite soil from an e-waste recycling site using five different artificial sweat formulations. Extractions were performed at temperatures ranging from 17 to 47 °C to investigate the effect of ambient temperature on bioaccessibility. Results obtained using the different artificial sweats were not consistent with one another. In particular, the NIHS 96-10 formulation solubilized larger amounts of analytes (ranging from 6.3 times the next most effective extractant for Cu to 1700 times the next most effective for Pb). There was a general increase in release of PTE with increasing temperature, except for As. Although trends varied between analytes and formulations, this highlights the need to consider ambient temperature when estimating dermal bioaccessibility of PTE in soil.